As idéias de Prigogine sobre irreversibilidade e indeterminação e suas consequências filosóficas - Carla Maria Pontes Carneiro (2003)
In this work, I present the ideas of Prigogine and Stengers about the metamorphosis of science which are developed in their book "A Nova Aliança". I attempt to show how it reflects the transition to a new world view: from a determinist and reducionist nature to an indeterministone, characterized by instabilities and complexities. In order to illustrate the controversial aspect of these ideas, I present two divergent positions about them. The first one refers to Jean Bricmont's criticism about the improper use of scientific concepts and the second one refersto the work of Fritjof Capra who attempts to establish a new order for the natural phenomena on the basis of the contributions of Prigogine and Stengers.